Acute and Sub-Acute Oral Toxicity Assessment of Marchantia paleacea Bertol. Liverwort Herb Extract in Mice on Liver and Kidney Function - Dicki Bakhtiar Purkon; Aurelya Veny Kurnia Nainggolan; Padmasari Diah Ayu Kumala Ningsih; Mimin Kusmiyati; Yayat Sudaryat; Ine Srinati; Faizah Min Fadhlillah; Hafizah Ilmi Sufa; Alni Khusnul Hotimah (Sanata Dharma University, 2025)
Herbaceous liverwort Marchantia paleacea Bertol. has been known as a potential source that has bioactive compounds with various pharmacological benefits, such as: antimicroorganism, antifungal, antioxidant, immunomodulator, hepatoprotector, antipyretic, diuretic, cardiotonic, and vasorelactan. However, information regarding oral acute and sub-acute toxicity data from ethanol extracts of Marchantia paleacea Bertol. liverwort herb is still very limited. Therefore, this study aimed to evaluate the acute and sub-acute toxicity of liverwort herb ethanol extract in female mice of ddY strains. The acute toxicity test method was carried out by giving ethanol extract of the liverwort herb Marchantia paleacea Bertol. (EEMP) in single doses at doses of 250, 500, 1000, and 2000 mg/kg bw orally for 14 days, while sub-acute toxicity tests were performed by administering EEMP test extracts at doses of 125, 250, 500, 1000, and 2000 mg/kg bw orally for 28 days in accordance with testing standards from BPOM (2022), Thompson-Weil, and OECD. Parameters observed include clinical symptoms (including: mortality), profile of body weight changes, biochemical analysis of serum, and histopathological analysis of vital organs (liver and kidney). Results from acute toxicity testing showed that a single dose of EEMP at the tested level did not cause significant clinical symptoms and histopathological disorders, and there were no deaths in test animals classified as mild toxic substances based on BPOM criteria ( 2000 mg/kg bw). And sub-acute toxicity tests from the 125, 250, and 2000 mg/kg bw test groups revealed a significant increase in average SGOT levels compared to the normal control group on the 28th test day (p0.05) but still within the normal range. Most other test parameter profiles show no significant changes. Some of the observed changes, particularly in the biochemical and histological parameters of the organs that occur are assumed to be transient reaction effects and are not a sign of toxicity. These findings suggest the need for further study of the potential toxic effects of the liverwort herb Marchantia paleacea Bertol. This study provides important insights in the understanding of the potential uses of the liverwort herb Marchantia paleacea Bertol. as a product of herbal ingredients (nutraseutics, supplements, and traditional medicine), and reinforces the need to understand the potential toxicity risks associated with it.